If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35p + 70q = 0 Solving 35p + 70q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-70q' to each side of the equation. 35p + 70q + -70q = 0 + -70q Combine like terms: 70q + -70q = 0 35p + 0 = 0 + -70q 35p = 0 + -70q Remove the zero: 35p = -70q Divide each side by '35'. p = -2q Simplifying p = -2q
| 14n+(x+3)=10 | | -36=4u-8 | | 6(x-3)+10=3(3x-4) | | 2t-6=17 | | 1x+2=14+2x | | (2x-6)/(9x)/(5x-15)/(3) | | X=5x*3+4 | | x^4+15x^3+19x^2-70=0 | | 9+5lnx=34 | | 2(5y-4)=3(y+0.8)-2 | | 3x-7x+22=-14 | | 2x+150+5x+121=180 | | 5x+19=11x+1 | | 3x=182 | | x^4+21x^3+9x^2+7=0 | | -f+2-7f=18 | | 3(x+8)+10=5(x-2)-(x-2) | | -250+19.50=-55 | | 6m+-4=m+11 | | 6x+158+8x+232=180 | | 3x+2-4x+7+3b+5b-2= | | -6f-13+4f=-11 | | 3x+13+6x-2= | | 11x^4+51x^3+9x^2+7=0 | | -27=r/12=19 | | (3x+13)+(6x-2)=y | | 4x+26=17 | | 11x^4+51x^2+97x=0 | | 2x+2iy=14i | | 2/3y-6=18 | | -2x(0)+y=1 | | 2x+14=60 |